1998
DOI: 10.3109/10826089809056256
|View full text |Cite
|
Sign up to set email alerts
|

Stressful Life Events and Adolescent Substance Use and Depression: Conditional and Gender Differentiated Effects

Abstract: Stressful life circumstances have myriad influences on human health and behavior. Early research focused on the variable distribution of stress and its effects by socioeconomic status, race, and gender. More recent research indicates that variation by age is also an important consideration. For example, adolescent reactions to stressful life events are often inconsistent with adult reactions to similar life situations and transitions. Moreover, since most studies assess only a single outcome--usually depressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
56
0
3

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(67 citation statements)
references
References 103 publications
8
56
0
3
Order By: Relevance
“…In fact, among men, none of the measures of alcohol consumption correlated with rumination, distraction, or depression. These findings are consistent with those of Hoffmann and Su (1998) who found that life events affected depressive symptoms and substance use among women but not among men. The cross-sectional design of this study limits the interpretation of its findings.…”
Section: Discussionsupporting
confidence: 94%
“…In fact, among men, none of the measures of alcohol consumption correlated with rumination, distraction, or depression. These findings are consistent with those of Hoffmann and Su (1998) who found that life events affected depressive symptoms and substance use among women but not among men. The cross-sectional design of this study limits the interpretation of its findings.…”
Section: Discussionsupporting
confidence: 94%
“…Strikingly, there are overwhelming data from human studies linking the cumulative impact of stressful life events that are unpredictable and long lasting during the juvenile years to behavioral abnormalities later on (Hoffmann and Su, 1998;Hoffmann et al, 2000). In this study, we asked whether chronic, variable stress during the previously uninvestigated peripubertal and juvenile periods leads to readily reversible effects or to more sustained effects in hippocampal structure (specifically, hippocampal principal cell layers) lasting into adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…Reports of studies of differential origins of drug ''abusing'' behaviors are sparse but suggest that social factors are more influential for females initiating drug use, and intrapersonal factors are more influential for males. [12,[23][24][25][26][27][28] If this is the case then are girls today experiencing more social pressures to use drugs than CHANGING PATTERNS OF U.S. DRUG USE 1239…”
Section: Convergence Of Prevalence Rates By Gendermentioning
confidence: 95%